Asymmetric Transfer Hydrogenation of 3-(Trifluoromethyl)quinolines - Guo, Ran-Ning; Chen, Zhang-Pei; Cai, Xian-Feng; Zhou, Yong-Gui (Synthesis, 2014)
A chiral phosphoric acid-catalyzed asymmetric transfer hydrogenation of 3-(trifluoromethyl)quinolines was successfully developed with up to 98% ee. The new method provides a direct and facile access to chiral 2,3-disubstituted 1,2,3,4-tetrahydroquinoline derivatives containing a stereogenic trifluoromethyl group.
Keywords: chiral phosphoric acid; transfer hydrogenation; quinolines; trifluoromethyl group